2006
DOI: 10.2350/06-03-0065.1
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for the Handling of Tissue Obtained by Operative Lung Biopsy: Recommendations of the chILD Pathology Co-Operative Group

Abstract: This is the first of a series on pediatric pulmonary disease that will appear as Perspectives in Pediatric Pathology over the coming months. The series will include practical issues, such as this protocol for handling lung biopsies and another on bronchoalveolar lavage in childhood, as well as reviews of advances in various areas in pediatric pulmonary pathology. It has been 11 years since the last Perspectives on pulmonary disease. Much has happened since then in this area, and this collection will highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 26 publications
(35 reference statements)
1
49
0
4
Order By: Relevance
“…Similar to experience with ILD in adults (2), a proportion of the biopsies were deemed nondiagnostic (12%), largely due to inadequate tissue sampling. To address this problem, a consensus protocol for handling tissue obtained at surgical lung biopsy has recently been published (40).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to experience with ILD in adults (2), a proportion of the biopsies were deemed nondiagnostic (12%), largely due to inadequate tissue sampling. To address this problem, a consensus protocol for handling tissue obtained at surgical lung biopsy has recently been published (40).…”
Section: Discussionmentioning
confidence: 99%
“…OLB has been the primary surgical approach in young children (120,121,132,133). However, VATS visualizes a greater percentage of the lung and permits the sampling of different lobes with the same incision sites (a consensus statement recommends multiple biopsy sites [134], even though there are limited data to support this approach [58]). Studies that have evaluated pediatric lung biopsy using VATS found less postoperative and long-term morbidity compared with OLB (16,135,136).…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…They are typically greater than 1 cm along each dimension in children (173) and up to 4 cm in adults (168), large enough for subdivision into separate portions for different purposes. Each portion should extend from the pleural base to the deepest part of the biopsy so that it is representative of the whole sample and not only a sub-region.…”
Section: Thoracoscopic and Open Lung Biopsymentioning
confidence: 99%